2012
DOI: 10.1152/ajpcell.00138.2012
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-sugar-sensing P2Y14 receptor promotes Rho-mediated signaling and chemotaxis in human neutrophils

Abstract: The G(i)-coupled P2Y(14) receptor (P2Y(14)-R) is potently activated by UDP-sugars and UDP. Although P2Y(14)-R mRNA is prominently expressed in circulating neutrophils, the signaling pathways and functional responses associated with this receptor are undefined. In this study, we illustrate that incubation of isolated human neutrophils with UDP-glucose resulted in cytoskeleton rearrangement, change of cell shape, and enhanced cell migration. We also demonstrate that UDP-glucose promotes rapid, robust, and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 56 publications
5
82
0
Order By: Relevance
“…3a, b). Similar effects of UDP-glucose were also observed after pre-treatment of UDP-glucose with apyrase to eliminate potential contamination with ATP/UTP [29] (not shown). Time-course experiments indicated that maximal PMN recruitment occurred within 12 h following UDPglucose instillation; neutrophil levels declined considerably after 24 h (Fig.…”
Section: Udp-glucose Promotes Neutrophil Lung Inflammationsupporting
confidence: 68%
See 4 more Smart Citations
“…3a, b). Similar effects of UDP-glucose were also observed after pre-treatment of UDP-glucose with apyrase to eliminate potential contamination with ATP/UTP [29] (not shown). Time-course experiments indicated that maximal PMN recruitment occurred within 12 h following UDPglucose instillation; neutrophil levels declined considerably after 24 h (Fig.…”
Section: Udp-glucose Promotes Neutrophil Lung Inflammationsupporting
confidence: 68%
“…UDP-glucose concentrations in control sputa were in the low nanomolar range (UDP-glucose 9.5 ± 2.1 nM) but increased up to 11-fold in CF (Fig. 1a), i.e., reaching concentration values capable of promoting P2Y 14 R-mediated responses [29]. Although the small sample size prevented us from establishing a correlation between UDP-glucose levels and lung function or sputum neutrophils within the CF group (Suppl.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations